Current trends in the development of business-education in Kazakhstan (experience and challenges) - Narynbayeva, A.S.; Korotkova, T.S.; Simanaviciene, Z. (BUKETOV BUSINESS REVIEW, 2020)
Object: The purpose of the research is to investigate global trends in business education, analyze the development of the business education system in the country, evaluate its current state, identification of factors that hinder the development of the domestic business education system, identification of existing problems and disadvantages, and suggestion of solutions to these problems. Methods: system, functional and statistical analyses, complex and historical approaches for studying the development of business education. Results: The results revealed that the system of business education in Kazakhstan has developed and is currently at the stage of development. In the context of a changing business environment and high competition in the domestic market of business education for the implementation of management personnel training programs, the need to investigate and take into account the needs and interests of employers, business schools, and program participants themselves is becoming increasingly relevant. This issue is considered in the research on the example of one of the promising direction of training of professional managers of “Master of business administration” (MBA) program. Conclusions: Based on the analysis of Kazakhstan and foreign sources, made research it is analyzed the latest developments of international business schools and the degree of their implementation in domestic practice, as well as offered suggestions for further improvement of the business education system, increasing the contribution of professional managers to ensuring sustainable development of the country’s economy and social sphere.